Devotional Foundations of Earthly Sovereignty: Conceptualizing Sovereignty and the Role of Devotion in Narrative Political Theology in Premodern India - Caleb Simmons (Religions, 2021)
The central premise of this article is that narrative literature from premodern India can give us insights into the ways that sovereignty was conceptualized within broader cosmological structures, creating what has been called “political theology” in other contexts. Looking to narratives for theology can give us particular insights into a tradition’s self-description. It is through narratives that Indian kings and their courts were able to describe the intentional-agential worlds of political hierarchies on a cosmic scale and situate themselves within this broader structure. This article, therefore, examines narratives from Purāṇas, particularly the Viṣṇu Purāṇa and the Dēvī Māhātmya, and dynastic foundational stories and genealogies from Karnataka found in vaṃśāvaḷis and epigraphic praśastis, using a twelfth-century Western Gaṅga inscription as an example, to see the political theologies from the premodern courts of India as they are articulated and performed in and between the realms of the divine and on Earth. After an examination of these materials, this article offers a new model to explain how premodern courts viewed their sovereignty vis-à-vis other divine and earthly sovereigns and how they understood the constitution, transfer, and diffusion of sovereignty throughout this cosmic spectrum of divine and earthly royalty through devotion and giving.